2021
DOI: 10.9734/jocamr/2021/v14i330246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin in Combination with a Herbal Capsule (Glucoblock) on Insulin Resistance and Oxidative Stress Index in Type 2 Diabetic Rats

Abstract: Aim: This study evaluated the effects of metformin in combination with a herbal capsule (glucoblock) on insulin resistance and oxidative stress index in type 2 diabetic rats. Methodology: A total of 35 male Wistar albino rats weighing between 120-220 g were used for this study. The rats were placed on high fat diet, and diabetes was induced by a single intraperitoneal injection of freshly prepared streptozotocin (STZ) (45 mg/kg body wt). Fasting plasma glucose (FPG) was determined using the glucose oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…It is presented as a suppression in metabolic responses of the liver, muscle, and adipose tissue to insulin action. It leads to impaired regulation of hepatic glucose synthesis, declining beta-cell function, ultimately leading to beta-cell failure [22]. This finding agrees with Tchaou et al [23], which showed that overnight fasting glucose was not influenced by monosodium glutamate (MSG) and Maggi poulet solution injection.…”
Section: N= Number Of Rats Ns= Not Significantsupporting
confidence: 69%
“…It is presented as a suppression in metabolic responses of the liver, muscle, and adipose tissue to insulin action. It leads to impaired regulation of hepatic glucose synthesis, declining beta-cell function, ultimately leading to beta-cell failure [22]. This finding agrees with Tchaou et al [23], which showed that overnight fasting glucose was not influenced by monosodium glutamate (MSG) and Maggi poulet solution injection.…”
Section: N= Number Of Rats Ns= Not Significantsupporting
confidence: 69%